Established and new rotavirus vaccines: a comprehensive review for healthcare professionals. Issue 1 (31st December 2022) - Vetter, Volker; Gardner, Robert C.; Debrus, Serge; Benninghoff, Bernd; Pereira, Priya
ABSTRACT: Robust scientific evidence related to two rotavirus (RV) vaccines available worldwide demonstrates their significant impact on RV disease burden. Improving RV vaccination coverage may result in better RV disease control. To make RV vaccination accessible to all eligible children worldwide and improve vaccine effectiveness in high-mortality settings, research into new RV vaccines continues. Although current and in-development RV vaccines differ in vaccine design, their common goal is the reduction of RV disease risk in children <5 years old for whom disease burden is the most significant. Given the range of RV vaccines available, informed decision-making is essential regarding the choice of vaccine for immunization. This review aims to describe the landscape of current and new RV vaccines, providing context for the assessment of their similarities and differences. As data for new vaccines are limited, future investigations will be required to evaluate their performance/added value in a real-world setting. PLAIN LANGUAGE SUMMARY: The disease Rotaviruses are a leading cause of acute diarrhea, also called gastroenterities, among young children. They can lead to servere dehydration, hospitilization, and even death. Several vaccines against rotavirus disease have been developed. Their design is based on: weakened human rotavirus that mimic natural infection without causing disease, such as Rotarix, Rotavin-M1, Rotavac and RV3-BB (not yet marketed) non-infective animal viruses such as RotaTeq, Rotasiil or LLR . new concepts, such as inactivated vaccines What is new? We reviewed the current, recently launched and soon-to-be-launched rotavirus vaccines and found that: Rotarix and RotaTeq have been used globally for more than a decade with demonstrated impact and favourable safety profile Limited data on the impact and safety profile are available to date for: Rotavin-M1 and LLR vaccines, locally marketed in Vietnam and China, respectively Rotavac and Rotasiil, licensed in india New vaccine concepts have been mainly investigated animal models with encouraging results What is the impact? Despite their different designs, the current rotavirus vaccines demonstrate effectiveness in protecting against rotairus gastroenterits. Data for most recent vacciness are currently limited, for which additional data are needed to demonstrate how they will perform on a larger scale, their added value in a real setting and ther safety profile.